2007
DOI: 10.1055/s-2007-965550
|View full text |Cite
|
Sign up to set email alerts
|

Korrelieren die klinischen, radiologischen und intraoperativen Befunde der Gonarthrose? Eine prospektive Studie an 103 Patienten

Abstract: The knee subscore appears to be an efficient method for staging the clinical progression of osteoarthritis of the knee for clinical practice as well as for clinical trials. The Womac score especially serves to record the level of pain. We were able to confirm that the presence of osteophytes is the most significant radiographic feature of osteoarthritis of the knee. The Kellgren score turned out to be a reliable method for monitoring the radiographic progression of osteoarthritis of the knee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
0
6
1
2
Order By: Relevance
“…In contradiction to this finding regarding the WOMAC domains, our results showed no significant differences or correlations between the three domains and the grades, assessed in groups, in the total study population [ 18 , 35 ]. In contrast to our findings, those of other studies have suggested that the WOMAC score and the K&L radiological grades are not correlated [ 16 , 18 ]; unlike in our study, most of the study populations in these studies were considered to have a K&L grade of 3.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contradiction to this finding regarding the WOMAC domains, our results showed no significant differences or correlations between the three domains and the grades, assessed in groups, in the total study population [ 18 , 35 ]. In contrast to our findings, those of other studies have suggested that the WOMAC score and the K&L radiological grades are not correlated [ 16 , 18 ]; unlike in our study, most of the study populations in these studies were considered to have a K&L grade of 3.…”
Section: Discussioncontrasting
confidence: 99%
“…According to Szebenyi et al [ 11 ], the likelihood of individuals with KOA presenting with pain or reduced function, as assessed by the WOMAC, is greater if these changes occur in the tibiofemoral (medial and/or lateral) and patellofemoral compartments at the same time rather than in one of these locations only, which was not assessed by Creamer et al [ 15 ]. In addition, pain was more strongly associated with specific changes caused by KOA [ 11 , 16 , 32 – 34 ]. Therefore, it seems that the type of change in the K&L scale is more effective in predicting pain and functional decline than the grade itself.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of the literature has shown disagreements between clinical variables and radiological investigations [1, 15, 2325]. In recent studies, it has been shown that the Kellgren-Lawrence score was not related to WOMAC score but that it was important to follow up the progress of the disease [26, 27]. The Framingham Osteoarthritis Study found that 10% of people aged 63 years and over had symptomatic knee OA in the presence of radiographic changes [1].…”
Section: Discussionmentioning
confidence: 99%
“…Few other authors also found similar results in their studies. 11,12 Our results have shown that the disability is positively associated with pain and stiffness in knee joint rather than X-ray findings. Similar results were illustrated in the studies conducted by McAlindon et al 13 and Jordan et al 14 that knee pain brings about more disability then the severity of osteoarthritis on knee radiographs.…”
Section: Discussionmentioning
confidence: 61%